2019
DOI: 10.1042/cs20190536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycophenolate and rapamycin on renal fibrosis in lupus nephritis

Abstract: Lupus nephritis (LN) leads to chronic kidney disease (CKD) through progressive fibrosis. Mycophenolate inhibits inosine monophosphate dehydrogenase and is a standard treatment for LN. The mammalian or mechanistic target of rapamycin (mTOR) pathway is activated in LN. Rapamycin inhibits mTOR and is effective in preventing kidney transplant rejection, with the additional merits of reduced incidence of malignancies and viral infections. The effect of mycophenolate or rapamycin on kidney fibrosis in LN has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Among the functions and pathways we have obtained, some functions or pathways have been proved to be involved in the regulation of pulmonary fibrosis, and some have not been reported. Inosine monophosphate (IMP) and uridine triphosphate (UTP) have not been found in IPF, but IMP is involved in the fibrotic process of lupus nephritis (LN) 41 . Whether the metabolic processes of IMP and UTP are involved in the process of pulmonary fibrosis awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the functions and pathways we have obtained, some functions or pathways have been proved to be involved in the regulation of pulmonary fibrosis, and some have not been reported. Inosine monophosphate (IMP) and uridine triphosphate (UTP) have not been found in IPF, but IMP is involved in the fibrotic process of lupus nephritis (LN) 41 . Whether the metabolic processes of IMP and UTP are involved in the process of pulmonary fibrosis awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative phosphorylation (OXPHOS) produces more than 95% of a cell's energy in the form of ATP mainly from mitochondrial one.Research found the association of common variants of the adenosine triphosphate 6q(ATP6) genes with SLE,which raises the possibility of a shared mitochondrial genetic background of LN [39].The mTOR mentioned above forms two distinct multiprotein complexes, mTORC1and mTORC2.mTOR is a serine/threonine kinase and expresses a phosphoinositide 3-kinase (PI3K)-related kinase family.The mTOR signaling pathway is closely associated with immune cells,the abnormalities of autophagy and OS,and plays an important role in the pathogenesis of LN.A clinical study found that rapamycin/sirolimus(mTOR Inhibitor),a drug currently approved to prevent organ transplant rejection,may offer a safe and effective treatment for lupus by blocking T cell function and decreasing mitochondrial dysfunction by activating mitophagy [40].The process is regulated by the autophagy-related gene family, While the atg5 gene has been linked to the development of LN by epigenetic studies. mTOR pathway guides the development of novel and effective therapies for patients with LN [41].The mitophagy pathway is an important form of autophagy for the selective removal of dysfunctional or redundant mitochondria.Pro cient mitophagy may have therapeutic effects in LN,and drugs that induce mitophagy,such as rapamycin works in exploration as therapeutic strategies to enhance the clearance of injury-promoting fragmented mitochondria and accelerate recovery from LN ares [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian or mechanistic target of rapamycin (mTOR) is an evolutionarily conserved serine-threonine kinase that plays a key role in the regulation of cell proliferation, metabolism, and survival. Increased mTOR activation is observed in patients and mice with LN 95 . Sirolimus is a naturally occurring macrolide antibiotic produced by Streptomyces hygroscopicus and is a specific inhibitor of the mTOR pathway.…”
Section: Mammalian or Mechanistic Target Of Rapamycinmentioning
confidence: 99%
“…There is also emerging evidence that the anti-proliferative property of mTOR inhibitors extends beyond lymphocytes to non-immune cells. We recently demonstrated that sirolimus decreased mesangial cell proliferation and their binding by anti-dsDNA antibodies and suppressed fibrotic responses in mesangial cells when cells were exposed to anti-dsDNA antibodies or transforming growth factor (TGF)-β1, and the effect was mediated through down-regulation of mTOR and extracellular signal-regulated kinase phosphorylation 95 . In NZB/W F1 mice with active nephritis, sirolimus was as effective as mycophenolate in attenuating kidney inflammation and fibrosis 95 .…”
Section: Mammalian or Mechanistic Target Of Rapamycinmentioning
confidence: 99%
See 1 more Smart Citation